2018
DOI: 10.14198/jhse.2018.134.13
|View full text |Cite
|
Sign up to set email alerts
|

How do psychological characteristics influence the sports performance of men and women? A study in school sports

Abstract: This study evaluates the psychological characteristics in sports performance according to gender and sports modality practiced in school sports. In addition, the possible correlations between the variables of the questionnaire of Psychological Characteristics related to Sports Performance (CPRD) (Gimeno, Buceta & Pérez-Llantada, 1994) are determined. in men and in women. The research follows a quantitative methodology of descriptive cut, through the survey. The sample size is 816 young athletes between 12 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…In addition, there are investigations which have been focused onto manifest differences between gender's player and the influence of their sports performances. Fradejas and Espada-Mateos (2018) affirm that men manifest higher levels of control over the influence of their own performances. Furthermore, same authors point that women are more concerned about their performances, which could be explained throughout high levels of competitive anxiety and low levels of self-confidence (Caputo, Rombaldi and da Silva, 2017;Fradejas and Espada-Mateos, 2018).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, there are investigations which have been focused onto manifest differences between gender's player and the influence of their sports performances. Fradejas and Espada-Mateos (2018) affirm that men manifest higher levels of control over the influence of their own performances. Furthermore, same authors point that women are more concerned about their performances, which could be explained throughout high levels of competitive anxiety and low levels of self-confidence (Caputo, Rombaldi and da Silva, 2017;Fradejas and Espada-Mateos, 2018).…”
Section: Introductionmentioning
confidence: 79%
“…Fradejas and Espada-Mateos (2018) affirm that men manifest higher levels of control over the influence of their own performances. Furthermore, same authors point that women are more concerned about their performances, which could be explained throughout high levels of competitive anxiety and low levels of self-confidence (Caputo, Rombaldi and da Silva, 2017;Fradejas and Espada-Mateos, 2018). Moreover, González, Campos and Romero (2014) found that more than two thirds (68%) of young footballers affirm that they were affected by negative external evaluations about their mistakes or performances.…”
Section: Introductionmentioning
confidence: 79%
“…Volleyball is a sport that can be played by children until people are old. The game of volleyball basically to 2 principles technical as well as psychic (Fradejas & Espada-Mateos, 2018). The technical principle is that the player turns the ball with the waist up, soaring in the air over the net to drop the ball on the opponent's field to find victory sportsmanship.…”
Section: Introductionmentioning
confidence: 99%
“…Extracurricular volleyball activities in inclusion schools generally have many challenges and do not go well because of the obstacles faced by students, one of which is the interest in volleyball [4][5][6]. Students' interest in volleyball is still lacking, it can be seen in students who rarely go to extracurricular exercises volleyball; therefore, students need to be given motivational direction about the importance of achievement so that practicing extracurricular volleyball is more enthusiastic and earnest [7][8][9].…”
Section: Introductionmentioning
confidence: 99%